Analysis of Neglected Justice in Land Disputes in Ambon District Court - Saija, Ronald (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The main task of a court judge is to receive, examine and adjudicate and settle every case that is brought to him. Judges may not refuse to examine and adjudicate cases submitted on the pretext that the law does not exist or is unclear, but is obligated to examine and try them. The study of this decision is to test whether the decision of the panel of judges in the court of first instance reflects a substantively fair decision.Purposes of the Research: The purpose of this study is to criticize the legal considerations of judges on land disputes objectively.Methods of the Research: The research method used is normative juridical research with a qualitative analytical descriptive nature, by examining legal materials, both primary legal materials and secondary legal materials through literature studies and other related literature.Results of the Research: The analysis used in this study is a qualitative analysis to answer the problems studied. The results of the research and discussion stated that the judge's decision in the District Court Decision Number 242/Pdt.G/2020/PN.Amb was wrong and neglected to provide legal considerations as legal objectives, namely aspects of justice, aspects of expediency and aspects of legal certainty. In these aspects, the judge was wrong and wrong in considering the ownership of a plot of land with an area of 267 M2 with a Certificate of Ownership in the name of the Defendant, namely Hana Marthina Leuhery Number 1739/desa rumah three, 15-05-2011, Letter of Measurement dated 5 May 2011 according to PRONA from the national land agency, so that aspects of justice, aspects of usefulness and aspects of legal certainty are neglected.